First-generation ESL calculus students’ beliefs about mathematical problem-solving - Palencia, Kevin; Duncan, Breille; Feliciano-Semidei, Ricela; Bustillo-Zarate, Alcibiades; Wu, Ke (American Journal of STEM Education, 2026)
This study investigates the mathematical problem-solving beliefs of first-generation calculus students using the Indiana Mathematics Belief Scale, with a particular focus on English as a Second Language (ESL) speakers. Two-tailed independent samples t-tests revealed that ESL students were less convinced of the practical usefulness of mathematics than their non-ESL first-generation peers, respectively. By identifying beliefs that support learning alongside those that may pose barriers, our findings provide a nuanced perspective on the calculus experiences of ESL first-generation students in STEM.